Landscape recovery in architecture teaching: readings from the valle de Aburra - Vélez Venegas, Claudia María; Montoya Arenas, Catalina; Escobar Ocampo, Lina María (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2019)
The dynamic nature and changes in the landscape of cities must be inherent to the teaching, research and practice of architecture. Latin American cities, with increasingly hybrid landscapes, are constituted by fragments of disconnected pieces that generate mixtures that are difficult to read and, why not, to value. To these manifestations is added the expansive pressure of the metropolis and, before it, a professional project practice that does not recognize the landscape as a determinant. They are forgotten landscapes, minimized, that in architecture teaching must be recover based on the recognition of the place that includes variables of landscape order, in this case linked to research questions: a task proposed as central in the set of formative investigations courses named Cultural Landscape at the Universidad Pontificia Bolivariana in Medellin. Thus, the architectural object that is intended to project, analyse and interpret its environment to generate forms and functions that establish a dialogue and respond to its context.
Keywords: Hybrid landscape; Place; Architecture; Formative research; Learning experiences